2020
DOI: 10.3390/nu12020303
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Two Water Extracts of Eleutherococcus senticosus Leaf and Rhizome of Drynaria fortunei Enhances Cognitive Function: A Placebo-Controlled, Randomized, Double-Blind Study in Healthy Adults

Abstract: We previously found that the water extract of Eleutherococcus senticosus leaves (ES extract) enhanced cognitive function in normal mice. Our study also revealed that the water extract of rhizomes of Drynaria fortunei (DR extract) enhanced memory function in Alzheimer’s disease model mice. In addition, our previous experiments suggested that a combined treatment of ES and DR extracts synergistically improved memory and anti-stress response in mice. Although those two botanical extracts are expected to be benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In cognitively healthy subjects, 5 intervention studies have evaluated the effect of fungi and algae extracts, other plant extracts, or combination of minerals and vitamins. A 12-week parallel intervention study in 31 cognitively healthy adults allocated to consume either a combination of an extract of Eleutherococcussenticosus (ES) and rhizomes of Drynariafortunei (DR) (203.01 mg/d of ES leaf extract, and 20.01 mg/d of DR), showed significant improvements in language, semantic fluency and figure recall scores [75]. Consumption of Hericiumerinaceus supplement (3.2 g/d) for 12 weeks also improved cognitive function and prevented cognitive decline in a study of 34 cognitively healthy subjects over the age of 50 years [76].…”
Section: Other Types Of Dietary Supplements (N = 15)mentioning
confidence: 99%
See 1 more Smart Citation
“…In cognitively healthy subjects, 5 intervention studies have evaluated the effect of fungi and algae extracts, other plant extracts, or combination of minerals and vitamins. A 12-week parallel intervention study in 31 cognitively healthy adults allocated to consume either a combination of an extract of Eleutherococcussenticosus (ES) and rhizomes of Drynariafortunei (DR) (203.01 mg/d of ES leaf extract, and 20.01 mg/d of DR), showed significant improvements in language, semantic fluency and figure recall scores [75]. Consumption of Hericiumerinaceus supplement (3.2 g/d) for 12 weeks also improved cognitive function and prevented cognitive decline in a study of 34 cognitively healthy subjects over the age of 50 years [76].…”
Section: Other Types Of Dietary Supplements (N = 15)mentioning
confidence: 99%
“…Other dietary supplements that have shown significant improvements on different cognitive domains are fungi and algae extracts (Hericiumerinaceus, Tremella fuciformis and Laminaria japonica), other plant extracts (Eleutherococcussenticosus leaf, Drynariafortuneirhizome, combined sage, rosemary and melissa, auraptene, astaxanthin and matured hop bitter acids), minerals such as magnesium, medium-chain triglycerides and the complex Twendee X (supplement containing a mix of eight antioxidants). The consumption of the above antioxidant and anti-inflammatory supplements not only significantly improved subjective memory complaints [84] and scores in different cognitive domains such as psychomotor and processing speed [73], working memory [76,77,79,81], short-term memory [74,76,77,84], spatial working memory [75,79,81,87], verbal episodic memory [78], verbal fluency [75,82,83], language [75,79,81,87], executive functions [79,82,84] and attention [79,83,87], but also cortical gray matter integrity in AD-related brain regions [84]. The spermidine-rich plant extract also had an impact on memory performance in subjects with SCD, although this was not significant, probably due to the small sample size (n = 30) and/or the short follow-up period (3 months) [85].…”
Section: Other Types Of Dietary Supplementsmentioning
confidence: 99%
“…Recently, a clinical study suggested that the water extract of ES leaves can enhance cognitive function in healthy adults without side effects (Tohda et al, 2020). A combined extract of ES leaves and Drynaria fortune rhizomes (DR) was administered to healthy volunteers over a period of 12 weeks, and the combined extracts significantly improved the language and memory abilities of the volunteers.…”
Section: Nds Relevant Pharmacological Effectsmentioning
confidence: 99%
“…We previously found that E. senticosus leaf extract and its constituents enhanced object recognition memory in healthy young mice [ 92 ]. The combination of DR and E. senticosus leaf extract has been investigated in healthy humans [ 93 ]. Healthy men and women were randomly divided into two groups, where one group (mean age was 63.0 years) took the combination, and the other group (mean age was 64.3 years) took a placebo for 12 weeks.…”
Section: Recovery From Aβ-induced Axonal Degenerationmentioning
confidence: 99%